'Propped and prone' positioning reduces respiratory events in spontaneously breathing preterm infants: A randomised triple crossover study. (31st October 2022) - Richmond, Christopher M; Ring, Fabian; Richmond, Lacey; Rossouw, Erika; Ballard, Emma; Birch, Pita
Abstract : Aim: We compared effects of infant positioning and feed‐rate interventions on respiratory events and oximetry parameters in spontaneously breathing preterm infants born <32 weeks gestation managed in a neonatal unit. Methods: A randomised triple crossover design was employed. n  = 68 infants underwent three test conditions A: control (supine/flat, gravity bolus feeds), B: position intervention (propped/prone) and C: feed‐rate intervention (continuous pump feeds) in randomised sequence over three consecutive days. Primary outcomes were number of events (apnoea, bradycardia and desaturation) and percentage time SpO2  < 80% over 24 h. The secondary outcome was percentage time SpO2  ≥ 88%. Treatment effects were estimated using linear mixed‐effects models. Results: Propped/prone positioning significantly reduced events and improved percentage time SpO2  < 80% and ≥88% compared to both other conditions (all P  < 0.001). Outcomes for the feed‐rate intervention were not significantly different to control. Conclusions: Alternative infant positioning should be considered in preterm infants managed in the neonatal unit.